2015
DOI: 10.1177/1948550615616170
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-Love or Self-Hate Predict Conspiracy Beliefs? Narcissism, Self-Esteem, and the Endorsement of Conspiracy Theories

Abstract: Across three studies, we examined the role of self-evaluation in predicting conspiracy beliefs. Previous research linked the endorsement of conspiracy theories to low self-esteem.We propose that conspiracy theories should rather be appealing to individuals with exaggerated feelings of self-love, such as narcissists, due to their paranoid tendencies. In Study 1 general conspiracist beliefs were predicted by high individual narcissism but low self-esteem. Study 2 demonstrated that these effects were differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
199
3
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(247 citation statements)
references
References 54 publications
(90 reference statements)
20
199
3
11
Order By: Relevance
“…Most importantly, while previous studies showed that CN was related to endorsement of specific conspiracy theories explaining particular hardships experienced by the in‐group (Cichocka et al., ; Golec de Zavala & Cichocka, ), the present study showed that CN predicts changes in the generic predisposition to think in conspiracy terms. Thus, while previous studies showed that CN predicts beliefs that specific out‐groups engaged in secretive, malevolent actions (Cichocka et al., ), our findings indicate that CN predicts a more general predilection toward conspiracy thinking—that is, an essentially content‐free tendency to believe that a malevolent, secretive “them” conspires against “us” to cause harm (Uscinski et al., ). Such results suggest that CN with reference to any in‐group should be related to general conspiracy thinking and in‐groups and out‐groups featured can be redefined depending on current intergroup context.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Most importantly, while previous studies showed that CN was related to endorsement of specific conspiracy theories explaining particular hardships experienced by the in‐group (Cichocka et al., ; Golec de Zavala & Cichocka, ), the present study showed that CN predicts changes in the generic predisposition to think in conspiracy terms. Thus, while previous studies showed that CN predicts beliefs that specific out‐groups engaged in secretive, malevolent actions (Cichocka et al., ), our findings indicate that CN predicts a more general predilection toward conspiracy thinking—that is, an essentially content‐free tendency to believe that a malevolent, secretive “them” conspires against “us” to cause harm (Uscinski et al., ). Such results suggest that CN with reference to any in‐group should be related to general conspiracy thinking and in‐groups and out‐groups featured can be redefined depending on current intergroup context.…”
Section: Discussioncontrasting
confidence: 73%
“…Consistent with the idea that conspiracy theories are especially appealing to those who feel they are losing politically (Uscinski & Parent, ), ideological liberalism was associated with growth in conspiracy thinking. Third, consistent with the idea that positive social identification is associated with reduced conspiracy endorsement once CN is accounted for (Cichocka et al., ), American identification was associated with decreased conspiracy thinking over the campaign.…”
Section: Resultssupporting
confidence: 58%
“…Furthermore, evidence suggests that belief in conspiracy theories is associated with problematic interpersonal relationships. Specifically, belief in conspiracy theories is correlated with a range of individual difference variables that reflect impoverished interpersonal functioning, such as interpersonal paranoia (Darwin et al., ), narcissism (Cichocka, Marchlewska, & Golec de Zavala, ), disagreeableness (Swami et al., ), insecure attachment (Green & Douglas, ) and Machiavellianism (Douglas & Sutton, ). While future research would need to examine the causal effects of conspiracy beliefs on the quality of interpersonal relationships more directly, the findings obtained so far are consistent with the idea that endorsing conspiracy theories is associated with poorer interpersonal functioning.…”
Section: Belief In Conspiracy Theories: Four Basic Principlesmentioning
confidence: 99%
“…Research examining CTs has increased dramatically in recent years, with much of it focusing on individual differences that predict increased endorsement of CTs or the circumstances under which conspiracy thinking is likely to emerge. For example, individuals who believe in CTs tend to have higher levels of paranormal beliefs (Swami et al., ), anxiety (Grzesiak‐Feldman, ), paranoid ideation (Darwin, Neave, & Holmes, ), openness to new experiences (Swami, Chamorro‐Premuzic, & Furnham, ), need for uniqueness (Imhoff & Lamberty, ; Lantian, Muller, Nurra, & Douglas, ), and narcissism (Cichocka, Marchlewska, & Golec de Zavala, ), and are lower in self‐esteem (Cichocka et al., ; Swami et al., ) and agreeableness (Swami et al., , ), and are more likely to believe in other CTs (Goertzel, ; Imhoff & Lamberty, ; Swami et al., , ), even when these beliefs are contradictory (Wood, Douglas, & Sutton, ). With respect to political antecedents, research indicates that CT endorsement is higher among those who are more politically extreme (van Prooijen, Krouwel, & Pollet, ) and politically cynical and distrusting of government (Swami et al., ).…”
Section: Individual‐difference Correlates Of Conspiracy Thinking and mentioning
confidence: 99%